Economic policy review - Federal Reserve Bank of New York (New York Federal Reserve Bank of New York, Research and Market Analysis Group, 1996)
The Review is a policy-oriented journal focusing on macroeconomic, banking, and financial market topics. It publishes new research by Federal Reserve Bank of New York economists, papers by affiliated economists, and the proceedings of Bank-sponsored conferences.
Keywords: Economics; ECONOMICS; ECONOMIC HISTORY; ECONOMIC POLICY; ECONOMIC CONDITIONS; USA; PERIODICALS; Federal Reserve Bank of New York